SISTEM INFORMASI PERENCANAAN DAN EVALUASI ANGGARAN BIAYA PRODUKSI MENGGUNAKAN PENDEKATAN METODE ACTIVITY BASED BUDGETING - Alvin Lisal; Asti Widayanti; Magdalena Karismariyanti (Universitas Mercu Buana, 2018)
As a manufacturing company before production, they should make production planning and calculate the production costs. One of the production cost planning tools are production budget. The company usually budgeting their production cost by prediction total cost, not consider the product, material, labour and mechine, its make company harder to evaluate the absorption of production budgets. Activity based budgeting method (ABB method) was a budgeting tools considering activity. The goal make this information system help company make production planning considering activity and evaluate company performance by evaluate the absosrption of budgeting (comparision between budget and realization). This information system built with the object-oriented method and development model with SDLC, use the programming language PHP and CodeIgniter framework. This system has the functionality to make production budget such as budgetary costs of raw materials, the cost of direct labor, and factory overhead costs based on the activity and also make transactions in accounting journals and ledgers and make realization budget reports and make comparison report between budget and realization and evaluating. The functionality of application has run 100% after tested with black box testing and user acceptance tests have been performed.